1971
DOI: 10.1113/jphysiol.1971.sp009459
|View full text |Cite
|
Sign up to set email alerts
|

The maintenance of resting potentials in glycerol‐treated muscle fibres

Abstract: 1. A modification of a previously published method for the disruption of the T‐tubules of frog skeletal muscle is described. The modification permits the disruption of the T‐tubules without the decline in resting potentials which was reported previously. 2. The method for the disruption of the T‐tubules involves the washout of glycerol following loading in a 400 m M glycerol Ringer solution. The modification consists of elevating the concentration of divalent cations in the Ringer used for glycerol washout. 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 11 publications
3
45
0
Order By: Relevance
“…Fig. 7A shows records obtained from a fibre detubulated according to the method of Howell & Jenden (1967) and Eisenberg, Howell & Vaughan (1971), for three different levels of depolarization which in a normal fibre would induce a slow inward current. All the detubulated fibres studied in these conditions were unable to develop …”
Section: Nature and Localization Of The Currentmentioning
confidence: 99%
“…Fig. 7A shows records obtained from a fibre detubulated according to the method of Howell & Jenden (1967) and Eisenberg, Howell & Vaughan (1971), for three different levels of depolarization which in a normal fibre would induce a slow inward current. All the detubulated fibres studied in these conditions were unable to develop …”
Section: Nature and Localization Of The Currentmentioning
confidence: 99%
“…3) was estimated to be 4-8 + 0 9 (absolute error) p-moles/cm2. Localization of the site of development of the calcium permeability Experiments were performed on four fibres detubulated according to the method of Howell & Jenden (1967) as modified by Eisenberg, Howell & Vaughan (1971). The results have shown that no calcium permeability can be elicited when T-tubules are disrupted (Fig.…”
Section: Effects Of High Concentration Of Calcium On the T-v Curvementioning
confidence: 99%
“…After soaking the muscle for 50 min at room temperature, an isotonic Ringer was introduced. Calcium and magnesium were elevated to 5 mm (Eisenberg, Howell & Vaughan, 1971 (Campbell, 1976 (Campbell, 1976) (Hodgkin & Horowicz, 1959;Armstrong & Lee, 1971;Venosa & Horowicz, 1973). It is known that for intact fibres at the resting potential, the chloride conductance is twice as large as the potassium conductance (Hodgkin & Horowicz, 1959).…”
Section: Methodsmentioning
confidence: 99%